ANALISIS KINERJA BERBASIS KONSEP VALUE FOR MONEY PADA KEGIATAN FISIK PEKERJAAN IRIGASI DONGGALA KODI (Study di Dinas Pekerjaan Umum Kota Palu) - Purwiyanti, Dwi (Katalogis, 2017)
This research intends to determine the performance of irrigation physical activiies of Donggala Kodi in 2014 based on: 1) economy ratio, 2) efficiency ratio, and (3)effectiveness ratio. This research is a descriptive by analyzing progress report of Irrigation project in Donggala Kodi in 2014. Data collection method is documentation and Data analysis tool is value for money concept. The results of the research concludes that the performance of Public Work Office on irrigation physical activity in Donggala Kodi in 2014 has been: 1) economically with economy ratio averagely under 100%; 2) efficiently conducted with efficiency averagely under 100%; 3) effectively conducted with effectivenessration of 100% in average.